2015
DOI: 10.9778/cmajo.20140025
|View full text |Cite
|
Sign up to set email alerts
|

Chronic health conditions reported by male inmates newly admitted to Canadian federal penitentiaries

Abstract: Background:International health studies have shown that inmates have higher rates of infectious diseases, chronic diseases and psychiatric disorders relative to the general population. We conducted a systematic collection of data on chronic physical health conditions reported by newly admitted inmates in Canadian federal penitentiaries.Methods: Over a 6-month period from April to September 2012, we collected and analyzed data from a standardized health interview routinely conducted with consenting incoming mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 12 publications
2
28
0
Order By: Relevance
“…4 International research reveals that people who experience incarceration have poor health compared with the general population, including higher rates of mental illness, substance use disorders, infectious diseases and injury. [5][6][7] An emerging body of literature identifies ways to improve health in this population, both in custody and after release, 8 and empirical and theoretical evidence suggests that such interventions could benefit all of society by decreasing health care costs, 9 improving health in the general population, [9][10][11][12][13][14] improving public safety 9 and decreasing reincarceration. 9,15,16 In Canada, there is a lack of data on many indicators of health for people who experience incarceration.…”
mentioning
confidence: 99%
“…4 International research reveals that people who experience incarceration have poor health compared with the general population, including higher rates of mental illness, substance use disorders, infectious diseases and injury. [5][6][7] An emerging body of literature identifies ways to improve health in this population, both in custody and after release, 8 and empirical and theoretical evidence suggests that such interventions could benefit all of society by decreasing health care costs, 9 improving health in the general population, [9][10][11][12][13][14] improving public safety 9 and decreasing reincarceration. 9,15,16 In Canada, there is a lack of data on many indicators of health for people who experience incarceration.…”
mentioning
confidence: 99%
“…[13][14][15] This finding has also been reported in Canada. 16,17 Four longitudinal studies examined the association between TBI and criminal justice involvement and focused on criminality and violent crime. [18][19][20][21] All suggested an association between TBI and criminal justice involvement, although results were not always significant.…”
mentioning
confidence: 99%
“…Although offenders did not report having chronic health problems at rates as high as those cited in American (Fazel and Baillargeon, 2011) and Australian (Indig et al, 2010) research with correctional samples, the study did confirm earlier research on infectious diseases within CSC (Zakaria et al, 2010) that had found that men and women in Canada's federal correctional system had higher rates of blood borne viruses than the general adult population. Preliminary analyses examining which subgroups of offenders within this population had poorer health indicated that men over 50 years of age reported higher rates of diabetes, prostate problems, cardiovascular problems, and arthritis than those under 50 years; Aboriginal men reported higher rates of blood borne viruses and head injury than non-Aboriginal men, and men with histories of IDU had higher rates of blood borne viruses than those who did not report IDU (Stewart et al, 2015).…”
Section: Introductionmentioning
confidence: 94%
“…Many health studies indicate that offenders have high rates of many chronic health conditions; in particular, rates of infectious diseases, brain injury, and psychiatric disorders are elevated relative to the general population (Fazel and Baillargeon, 2011;Harmon, 2012;McIsaac et al, 2016;Stewart et al, 2015;Wilper et al, 2009;Zakaria et al, 2010). Several factors may contribute to these elevated rates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation